O-010 Effective minimally invasive treatment of moderate lumbar spinal stenosis with the superion interspinous spacer. (16th November 2010) - Rappard, G; Block, J; Miller, L; Chiu, J; Bini, W
Abstract : Introduction and purpose: Mild lumbar spinal stenosis (LSS) is treated with conservative measures although long term success remains elusive. Patients with severe radicular symptoms often require surgical intervention. However, there is a significant therapeutic void for patients with moderate LSS. The purpose of this study was to evaluate the preliminary effectiveness and safety of the Superion Interspinous Spacer (Vertiflex, Inc, San Clemente, California, USA) in patients with moderate LSS. Materials and methods: This prospective study enrolled 121 patients (aged 58±14 years) with moderate LSS who were treated at EMMA Klinik (Seligenstadt, Germany) between February 2008 and August 2009 and followed-up at 1 (n=111), 3 (n=96), 6 (n=81) and 12 (n=52) months. Patients were treated with the Superion Interspinous Spacer, a minimally invasive spinal implant that limits back extension at the symptomatic level. Study outcomes included back function with Oswestry Disability Index, axial and extremity pain severity with a visual analog scale, health related quality of life with Physical Component Summary (PCS) and Mental Component Summary (MCS) scores from the SF-36, and adverse events. Results: Back function rapidly improved from pretreatment (60.2±7.9%) to 1 month (33.6±10.3%) with continued improvement through to 12 months (21.0±13.7%), a 64% overall improvement (p<0.001) (Abstract O-010 figure 1A ). Back function clinical success, defined as improvement of 30% or more from pretreatment values, was 92% at 12 months. Axial pain decreased at the 1 month visit (6.9±1.1 to 3.9±1.2) and this improvement was maintained through to 12 months (3.4±1.5), representing a 49% improvement (p<0.001). Similar improvements (53% overall, p<0.001) in extremity pain were observed (pretreatment: 6.6±1.4, 1 month: 3.3±1.4, 12 months: 2.8±1.5) (Abstract O-010 figure 1A ). Clinical success at 12 months using a 30% improvement criterion was 76% for axial pain and 86% for extremity pain. Health related quality of life improved 41% for PCS (26.9±4.5 at pretreatment to 39.2±6.1 at 12 months) and 22% for MCS (36.0±4.2 at pretreatment to 44.0±5.7 at 12 months) (both p<0.001) (Abstract O-010 figure 1B ). PCS clinical success (≥5.7 point improvement) was 81% and MCS clinical success (≥6.3 point improvement) was 62% at 12 months. Four (3.3%) explants were performed although three were unrelated to the device. Eight procedure related adverse events, observed in six (5.0%) patients, included superficial incision seroma (n=5), minor wound pain (n=2) and infection (n=1). Conclusion: The Superion Interspinous Spacer is an effective and safe treatment option for patients with moderate LSS who are unresponsive to conservative care.